PKM alat aquatic weed harvester dan pemberdayaan digitalisasi produk rumput laut pada Kelompok Pembudidaya Akbar Polman: Community service program for aquatic weed harvesting and digital empowerment of seaweed products for the Akbar Cultivation Community Polman - Ilham Ilham; Muhammad Nasrul; Muh Rafli Rasyid; Aldiansyah Aldiansyah; Aisyah Permadi; Abd Malik; Siti Padlia Alibas; Andi Rosman N; Niken Nur Kasim; Sri Sukmawati; Nurul Wirid Annisaa (Agriculture and Forestry Faculty, Universitas Sulawesi Barat, 2026)
One of the seaweed farming groups with strong development potential is the Akbar Cultivation Group, located in Lantora Village, Polewali District. This group has been operating for approximately seven years and is part of a seaweed production centre in Polewali Mandar Regency. The partner group’s main challenge lies in the production process. All stages of cultivation—from installing stretch ropes, maintenance, and inspection of farming installations to pulling ropes and harvesting seaweed—are still carried out manually without mechanical assistance. This condition requires a large workforce and relatively long working hours and poses higher safety risks, especially when the weather and sea wave conditions are unfavourable. Based on these circumstances, an empowerment program is needed to comprehensively address the group’s problems, from production to marketing. The implementation method uses a participatory and demonstration approach, which actively involves participants and provides hands-on practice in equipment operation. As a result of this program, 15 participants showed high enthusiasm during the training activities, and there was a significant improvement in their understanding and skills related to aquatic weed harvester technology and digital marketing. Prior to the training, participants’ knowledge and skills, measured through a pre-test questionnaire, averaged only 32.15%, with a score of 1.87 on a scale of 5. However, after the training and post-test evaluation, their knowledge and skills increased to an average of 88.00%, with a mean score of 4.4 out of 5. These data indicate that the participants’ knowledge and skills improved by 55.85% after the program.